Motion and Gender-Typing Features Interact in the Perception of Human Bodies - D’Argenio, Giulia; Finisguerra, Alessandra; Urgesi, Cosimo (Frontiers in Neuroscience, 2020)
The human body conveys socially relevant information, including a person’s gender. Several studies have shown that both shape and motion inform gender judgements of bodies. However, while body shape seems to influence more the judgement of female bodies, body motion seems to play a major role in the judgements of male bodies. Yet, the interdependence of morphologic and dynamic cues in shaping gender judgement and attractiveness evaluation in body perception is still unclear. In 2 experiments, we investigated how variations of implied motion and shape interact in perceptual and affective judgments of female and male bodies. In Experiment 1, participants were asked to provide ratings for masculinity and femininity of virtual renderings of human bodies with variable gender-typing features and implied motion. We found evidence of a tendency to perceive bodies in static poses as more feminine and bodies in dynamic poses as more masculine. In Experiment 2, participants rated the same pictures for dynamism and pleasantness. We found that male bodies were judged more dynamic than female bodies with the same pose. Also, female bodies were liked more in static than dynamic poses. A mediation analysis allowed us to further shed light on the relationship between gender-typing features and motion, suggesting that the less is the movement conveyed by a female body the greater is an observer’s sensitivity to its femininity, and this leads to a more positive evaluation of its pleasantness. Our findings hint to an association between stillness and femininity in body perception, which can stem from either the evolutionary meaning of sexual selection and/or the influence of cultural norms.